Partnership For Peace, Tackling The Threats And Raising The Prospects For Justice In Rivers State - Allen, Fidelis (Advances in Social Sciences Research Journal, 2016)
United Nations World Peace Day 2015 was marked with the theme, Partnership for Peace: Dignity for All. This is significant in many ways. First, it drew the attention of civil society groups, governments and all in positions of authority to the urgent need for strengthening collaborative security in a world peppered with violent conflict. Second, deep reflection on the human condition as the basis of analysis of any effort at securing lives and properties, and ensuring peace at the domestic and global fronts, was again brought to the fore. It sent a powerful message of a global quest for peace in a world, where injustice, wars, and relationships have become more and more defined by strong-arming. It is argued here that injustice lies at the heart of many violent conflicts. Injustices of elite greed, struggle for power and sharp social and economic inequality in society, have promoted human conditions that are conducive to disharmony, disorder and wars. Peace cannot be secured by increased funding for the purchase of ammunitions or weapons of war alone. Instead, to reduce violent conflict, crime and rebellion, the question of economic, social and political inequality has to be addressed. Peace is the result of commitment of all to justice, which has to be defined in terms of respect for human rights and responsiveness to human security needs. Further, which is the main point of this paper is, collaborative tackling of threats to peace is a crucial element in securing justice in a society like Rivers State, where many social, political and economic tendencies have played out in recent times.